Large-Scale Comparative Analysis of Eugenol-Induced/Repressed Genes Expression in Aspergillus flavus Using RNA-seq - Lv, Cong; Wang, Ping; Ma, Longxue; Zheng, Mumin; Liu, Yang; Xing, Fuguo (Frontiers in Microbiology, 2018)
Aflatoxin B1 (AFB1), which is mainly produced by Aspergillus flavus and Aspergillus parasiticus, is the most toxic and hepatocarcinogenic polyketide known. Chemical fungicides are currently utilized to reduce this fungal contaminant, but they are potentially harmful to human health and the environment. Therefore, natural anti-aflatoxigenic products are used as sustainable alternatives to control food and feed contamination. For example, eugenol, presents in many essential oils, has been identified as an aflatoxin inhibitor. However, its exact mechanism of inhibition is yet to be clarified. In this study, the anti-aflatoxigenic mechanism of eugenol in A. flavus was determined using a comparative transcriptomic approach. Twenty of 29 genes in the aflatoxin biosynthetic pathway were down-regulated by eugenol. The most strongly down-regulated gene was aflMa, followed by aflI, aflJ, aflCa, aflH, aflNa, aflE, aflG, aflM, aflD and aflP. However, the expression of the regulator gene aflR did not change significantly and the expression of aflS was slightly up-regulated. The down-regulation of the global regulator gene veA resulted in the up-regulation of srrA, and the down-regulation of ap-1 and mtfA. The early developmental regulator brlA was profoundly up-regulated in A. flavus after eugenol treatment. These results suggested a model in which eugenol improves fungal development by up-regulating the expression of brlA by the suppression of veA expression and inhibits aflatoxin production through the suppression of veA expression. Exposure to eugenol also caused dysregulated transcript levels of the G protein-coupled receptors and oxylipins genes. A Gene Ontology analysis indicated that the genes that were highly responsive to eugenol were mainly enriched in RNA-binding functions, suggesting that post-transcriptional modification plays a pivotal role in aflatoxin biosynthesis. KEGG analysis showed that ribosome biogenesis was the most dysregulated pathway, suggesting that eugenol dysregulates ribosome biogenesis, which then interrupts the biosynthesis of Nor-1, Ver-1 and OmtA, and prevents aflatoxisomes performing their normal function in aflatoxin production. In conclusion, our results indicated that eugenol inhibited AFB1 production by modulating the expression of structural genes in aflatoxin pathway, fungal antioxidant status, post-transcriptional modifications and biosynthesis of backbone enzymes in A. flavus.